Census of Governments, 1962 and 1967 ([Verlag nicht ermittelbar], 1984)
This study contains economic and employment data at the county level for states and local governments in the United States in 1962 and 1967. Data are provided on total population, land area, general revenues, number of municipalities and local governments of all types, number of public school districts, and number of employees of local governments. Information is also provided on educational payrolls of local governments, average earnings of full-time teachers, water supply revenues and expenditures of local governments, local government general expenditures on public welfare, highways, health and hospitals, police and fire protection, natural resources, and urban renewal, long-term general debt outstanding of local schools and local governments, and per capita intergovernmental revenues and expenditures.